Noise Reduction in DECT Images using spatial neighboring density method using bilateral filter - Sharma, Pallavi; Tiwari, Vibha (International Journal of Computer Sciences and Engineering, 2025)
the Dual-energy computed tomography (DECT) has got high popularity in the field of medical. By using DECT we can easily check or capture the body organs. Noise reduction is the premier process in the x-ray field or the medical imaging field. In this analysis we present the study of DECT images. The images which have the high material density they have more noise as well. To make image appearance better the noise reduction should be done. The use of filter is a primary tool in image noise correction. The non-linear filter removes the noise problem in the image. We are using bilateral filter to remove the noise in DECT images. This paper enlights different method of noise reduction in DECT images and the result will compare with the help of MATLAB software. ImaSim Software provides ability to present and manipulate CT data.